Gender Representation on Pictures, Dialogues and Reading Texts in â€œBahasa Inggris Untuk Kelas X SMA/Maâ€. - Murrikaningrum, Devi Arini; Mujiyanto, Januarius; Saleh, Mursid (Universitas Negeri Semarang, 2021)
This study focuses on gender representation of the picture, dialogue, and reading texts in a textbook â€“ Bahasa Inggria Untuk Kelas X SMA/MA. For Grade X Senior High School. It used a descriptive qualitative approach, and its objective was both to investigate gender representation in the pictures, dialogue, and reading text and, the representation between them. The study revealed that male domination was found in the picture, dialogues and, reading text as seen from gender visibility, gender-specific nouns, gender-stereotypes. Only, in the dialogues gender stereotype was dominated by female. The relation between picture, reading text and, dialogues, have similarity was dominated by a male, as seen from gender-neutral and gender-specific nouns. Although gender stereotypes and gender visibility in the dialogue were dominated by a female. Gender visibility, gender stereotype, gender-neutral and gender-specific noun between reading texts and pictures, have similarity was dominated by male. The representation between reading text and pictures support each other because they are mutually sustainable. Gender visibility and gender stereotype in the reading text and dialogue have unequal dominated. Gender visibility in the reading text is dominated by a male, while gender visibility in the dialogue is dominated by a female.